Income Analysis and Feasibility of Peanut Farming (Arachis hypogaea L) in Seakasale Village, East Taniwel Subdistrict, Seram Bagian Barat Regency - Sawaule, Christin; Riry, Johan; Riry, Roberth Berthy (Universitas Pattimura, 2024)
The peanut plant (Arachis hypogaea L.), which has now become widely cultivated and a primary choice for farmers in Indonesia, is not native to Indonesia. This research was conducted in Seakasale Village, East Taniwel District, West Seram Regency. A systematic approach was used to gather information from respondents. The highest production costs for peanut farmers in Seakasale Village were incurred by three respondents, A.S, D.L, and L.E, with a total cost ranging from Rp. 6,160,000 to Rp. 6,890,000. The lowest production costs were reported by seven respondents, H.L, Y.L, F.M, M.S, A.M, A.S, and I.A, with total costs ranging from Rp. 4,400,000 to Rp. 4,900,000. Two respondents, A.S. and A.M., reported the highest peanut farming income in Seakasale Village, with a total income of Rp. 15,000,000. One respondent, L.E, reported the average income with a total of Rp. 11,250,000, while the lowest income was reported by seven respondents, H.L, Y.L, F.M, D.L, A.S, I.A, and L.A, with a total of Rp. 7,500,000. Based on the B/C ratio analysis, the calculations indicate that the ten respondents listed above have a B/C ratio of less than 1, meaning their peanut farming ventures are unviable and require improvements.